Influence of hydrogel spacer placement with prostate brachytherapy on rectal and urinary toxicity - Achiraya Teyateeti (2022)
Objective: To determine the influence of rectal hydrogel spacer placement (HSP) on late rectal toxicity outcomes in prostate cancer patients treated with low-dose-rate (LDR) brachytherapy, with or without supplemental external beam radiotherapy (EBRT). Patients and Methods: A total of 224 patients underwent LDR brachytherapy with HSP, as monotherapy or combined with EBRT, between January 2016 and December 2019. Dosimetric variables reflecting the extent of rectal sparing and late rectal toxicity outcomes were evaluated. This spacer cohort was retrospectively compared to a similar patient group (n = 139) in whom HSP was not used. Results: Hydrogel spacer placement was associated with significantly reduced rectal doses for all dosimetric variables; the median percentage rectal dose to 1 cc of rectum and rectal dose to 2 cc of rectum of the spacer cohort were all significantly lower compared to the non-spacer cohort. The incidence rates of overall (any grade) and grade ≥2 rectal toxicity were lower in patients with HSP compared to patients who did not undergo HSP: 12% and 1.8% vs 31% and 5.8%, respectively. The 3-year cumulative incidence of overall rectal toxicity was significantly lower with HSP than without (15% vs 33%; P < 0.001), corresponding to an overall rectal toxicity reduction on univariable analysis (hazard ratio 0.45, 95% confidence interval 0.28–0.73; P = 0.001). In this patient cohort treated with prostate brachytherapy, none of the urethral dosimetric variables or the presence or absence of HSP was associated with late urinary toxicity. Conclusion: Hydrogel rectal spacer placement is a safe procedure, associated with significantly reduced rectal dose. HSP translates to a decrease in overall late rectal toxicity in patients receiving dose-escalated brachytherapy-based procedures.